2005
DOI: 10.1177/003335490512000615
|View full text |Cite
|
Sign up to set email alerts
|

Child Labor and Musculoskeletal Disorders: The Pelotas (Brazil) Epidemiological Survey

Abstract: SYNOPSISObjectives. This article describes the prevalence of musculoskeletal pain in several anatomic sites in children and teens, and investigates, while adjusting for potential confounders, the association between musculoskeletal pain and back pain and the following: age, gender, sports practice, use of computer/video games/television, school attendance, intensity of involvement in household domestic activities, care of other children, care of sick/elderly family members, work activities, and workloads.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
17

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 11 publications
1
50
0
17
Order By: Relevance
“…After the screening process (titles, abstracts, and full text reading), 18 studies 34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51 (with a population of 19,387 individuals and samples varying from 56 to 3,269 participants 34,39 ) met the inclusion criteria. Figure 1 shows flow diagram of this review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the screening process (titles, abstracts, and full text reading), 18 studies 34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51 (with a population of 19,387 individuals and samples varying from 56 to 3,269 participants 34,39 ) met the inclusion criteria. Figure 1 shows flow diagram of this review.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies included males and females, ranging from children 39 to the elderly 50 , with populations residing in urban and rural areas 44 , but none showed separate prevalence values according to gender. Three studies 34,36,44 reported on the prevalence of low back pain exclusively in women, two of which presenting the rates observed in female urban workers 34,36 and one in female farm laborers 44 , but the different prevalence periods prevented any comparison.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Obter informações de crianças e familiares sobre trabalho infantil e conhecer seus efeitos sobre a saúde é um desafio, mas algumas evidências já apontam que tais impactos podem ser mais prejudiciais quanto menor a idade da criança, maior interferência em atividades escolares, maior jornada de trabalho e maior a exposição a riscos ocupacionais 38 . Estudos nacionais encontraram a associação entre trabalho infantil e dores musculoesqueléticas 39 ; problemas comportamentais (que poderiam envolver agressividade, ansiedade e depressão) 40 e maior chance de sofrer agressão física e ferimentos; sentir-se só 41 e ter problemas de sono 41,42 .…”
Section: Discussionunclassified